THE ROLE OF AUTOMOTIVE TRANSPORT IN AIR POLLUTION OF THE ATMOSPHERE - Ikramova Nargiza Alisher qizi (American Journals Publishing, 2024)
This article is dedicated to studying the contribution of automotive vehicles to air pollution in the atmosphere. The harmful gases emitted by automobiles negatively impact the environment and pose a threat to human health. The issue is discussed in detail based on global experiences and statistical data. Recommendations are provided for reducing pollution levels.
Keywords: Atmospheric air, automotive transport, environmental issues, harmful emissions, pollution, sustainable development